Linguistic aspects of concepts of law in Chinese legal discourse - Chan, Clara Ho-yan; Galdia, Marcus (Comparative Legilinguistics, 2025)
Chinese concepts of law have been rarely approached from the legal-linguistic perspective. Systematic research into the Chinese law started with the analysis of the traditional concept of law in Chinese state and society. Scholarly interest in this perspective was mainly conditioned by the question whether the Chinese concept of law differs from Occidental conceptions. In terms of legal-linguistic research, the answer to this traditional question depends on the methodology used in scrutinizing legal Chinese, both in the diachronic and in the synchronic perspectives. This methodology is rooted in the analysis of the Chinese legal discourse. It indicates a complexity of concepts and related argumentative structures that was underestimated by the traditional research. Therefore, in this study the stages in the development of the discourse about Chinese concepts of law are elucidated to show their dependance upon the legal discourse in its different stages of social evolution. Nowadays, the traditional concept of law plays a limited role in the Chinese legal discourse. Today, Occidental conceptions of law dominate the legal landscape of the Chinese-speaking world. Therefore, the understanding of discursive fundamentals necessitates the integration of both research areas. Finally, the focus upon the language of law rather than the traditional concept may enable new insights into the nature of the discourse about the Chinese law. This study investigates the preconditions of such innovative insights.